The effects of nature sound in open-plan office on perceived psychological restoration and cognitive performance - Munirah binti Ahmad Dahari (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International islamic University Malaysia, 2017)
Studies in the area of psychological restoration at the workplace tend to focus on the positive effects of visual natural environments, and limited work has been carried out to explore the potential role that natural auditory stimuli could play in facilitating this process within open-plan office settings. Addressing this gap, the present study investigates the effects of nature sounds and office noises on perceived psychological restoration and cognitive performance of workers in an open-plan office. The study, which took place in the Registry Office at the University Putra Malaysia, involved a total of 50 administrative workers (Males = 15; Females = 35). Using a within-subject repeated measure design, all participants were exposed to four auditive stimuli (geophony, machine-generated noise, biophony, and human-generated noise) for the duration of one month following a specially designed schedule. At the end of each week, participants completed a questionnaire that consisted of background information, the Perceived Restorativeness Scale, and an error detection task. Results of two separate one-way repeated measure ANOVAs revealed that: (1) there is a significant positive effect of nature sounds, specifically the biophony, on perceived psychological restoration; (2) a significant negative effect of office noises, specifically human-generated noise, on perceived psychological restoration; (3) a significant positive effect of nature sounds on cognitive performance; and (4) a significant negative effect of office noises on cognitive performance. Taking these findings together, it can be concluded that exposure to nature sounds, particularly biophony, can bring positive effects to people cognitively and psychologically. In contrast, exposure to office noise, particularly human-generated ones, has significant negative effects on cognitive performance and perceived psychological restoration. Further discussions on the results are presented, together with the implications of the present study and the recommendations for future research.